Caracterização hidrossedimentológica de uma microbacia hidrográfica agrícola na Amazônia Legal - Menon, Rafael Alberto (2015)
The water resources management has among its activities the monitoring and characterization of the use and occupation of soil and water basins, as well as its effects on the aquatic ecosystem. The Amazon region, specifically the Teles Pires Basin, has been planned for use of its waters for several projects of electricity generation, with several dams in the planning stages, licensing or construction. The effectiveness of these processes involves hydrosedimentological study in a watershed. So the aim of this study was to monitor the sediment discharge suspended and bottom of a watershed in the Amazon region, in order to quantify the dry cargo this area and correlate with the use and occupation of the region. The liquid discharge and solid discharge suspended through various campaigns are using the methodology of equal increment of width was monitored (IIL) to collect water samples. There was good correlation of the rating curve and liquid and solid discharge, and although this watershed has a low solid discharge, and so on down state of environmental degradation. Also sought to quantification of total sediments and the Colby method validation for the basin. This method was not effective, overestimating average 32,15ton.dia-1 .